2009
DOI: 10.1097/qai.0b013e3181b17f53
|View full text |Cite
|
Sign up to set email alerts
|

Raltegravir, Etravirine, and Ritonavir-Boosted Darunavir: A Safe and Successful Rescue Regimen for Multidrug-Resistant HIV-1 Infection

Abstract: The combination of raltegravir, ETR, and DRV/r was a highly effective and well-tolerated antiretroviral salvage regimen in patients infected with multidrug-resistant HIV-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 17 publications
4
37
0
1
Order By: Relevance
“…This viral load suppression was remarkable for patients infected with HIV-1 that has triple-class drug resistance and in whom therapy had failed previously. As observed in our study, the efficiency of darunavir, etravirine and raltegravir in MDR HIV-1 infected patients has been previously reported [8,15]. It has been shown that in patients infected by MDR HIV-1 with few remaining treatment options, the optimized background therapy combined with these new molecules had a rapid and potent antiretroviral effect that was superior to the effect of optimized background therapy [8,15].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This viral load suppression was remarkable for patients infected with HIV-1 that has triple-class drug resistance and in whom therapy had failed previously. As observed in our study, the efficiency of darunavir, etravirine and raltegravir in MDR HIV-1 infected patients has been previously reported [8,15]. It has been shown that in patients infected by MDR HIV-1 with few remaining treatment options, the optimized background therapy combined with these new molecules had a rapid and potent antiretroviral effect that was superior to the effect of optimized background therapy [8,15].…”
Section: Discussionsupporting
confidence: 78%
“…The difficult-to-treat-patients developing MDR HIV infection have high experience with antiretroviral therapy and no therapeutic option with all disposed antiretroviral drugs was possible. Recently, three molecules, darunavir/ritonavir, etravirine and ralté-gravir were proposed in the treatment of HIV infected patients [6][7][8][9][10][11][12][13][14][15]. In this study, we analyzed the efficiency of these new drugs combined to optimized background therapy during twelve months in patients with advanced MDR HIV-1 infection and treatment failures with the three classes of antiretroviral drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation of lower rates of adverse events in the DRV/r and PI-Sparing treatment strategies echo the favorable safety profiles for post-2006 treatment options reported in recent clinical trials. [2][3][4][6][7][8][9][10][11][12] The results of this study should be interpreted within the context of its limitations. As a single academic HIV clinic in the Southeastern USA, results may not be generalizable to other locations.…”
Section: Discussionmentioning
confidence: 91%
“…With various clinical trials highlighting the safety and superior efficacy of these newer agents, complete virologic suppression has become the therapeutic goal for all HIV-infected patients, including those who are treatment-experienced. [1][2][3][4][5][6][7][8][9][10][11][12] Despite the accumulating body of evidence from clinical trials, a paucity of published data addressing the effectiveness of these newer agents in routine clinical care settings exists. Evaluating both the efficacy and effectiveness of newer agents is important to ensure that the results obtained from clinical trials are generalizable to populations treated through routine care.…”
Section: Introductionmentioning
confidence: 99%